Surface enhanced infrared absorption of nucleic acids on gold substrate - Dovbeshko, G.I.; Chegel, V.I.; Gridina, N.Y.; Repnytska, O.P.; Shirshov, Y.M.; Tryndiak, V.P.; Todor, I.M.; Zynio, S.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Data on surface enhanced infrared absorption (SEIRA) of nucleic acids deposited on the metal surface have been obtained in the experiment in FTIR reflectance mode. As metal surface, we used Au of 200-500 Е thickness on glass substrate. Roughness of Au was about 50 Е. In our experimental conditions, the enhancement factor of SEIRA was 3 to 5. We obtained different enhancement factors for different vibrations of nucleic acids. Application of this method to tumour nucleic acid gave a possibility to reveal some structural peculiarities of their sugar-phosphate backbone and those after application of anti-cancer drugs.